Eda ǝlǝ terudu bǝjumǝciwkǝ - Rahmanin, Gr. (Selhozgiz, 1933)
Apskats par medībām Sibīrijā. Teksts evenku valodā.
Почему надо охотиться в срок?
Keywords: Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Animal production; Hunting; Tungus languages; Evenki language; Medības; Evenku valoda